Measuring protection of aromatic wine thiols from oxidation by competitive reactions vs wine preservatives with ortho-quinones - Nikolantonaki, M.a; Magiatis, P.b; Waterhouse, A.L.a (Food Chemistry, 2014)
Quinones are central intermediates in wine oxidation that can degrade the quality of wine by reactions with varietal thiols, such as 3-sulfanylhexanol, decreasing desirable aroma. Protection by wine preservatives (sulphur dioxide, glutathione, ascorbic acid and model tannin, phloroglucinol) was assessed by competitive sacrificial reactions with 4-methyl-1,2-benzoquinone, quantifying products and ratios by HPLC-UV-MS. Regioselectivity was assessed by product isolation and identification by NMR spectroscopy. Nucleophilic addition reactions compete with two electron reduction of quinones by sulphur dioxide or ascorbic acid, and both routes serve as effective quenching pathways, but minor secondary products from coupled redox reactions between the products and reactants are also observed. The wine preservatives were all highly reactive and thus all very protective against 3-sulfanylhexanol loss to the quinone, but showed only additive antioxidant effects. Confirmation of these reaction rates and pathways in wine is needed to assess the actual protective action of each tested preservative. © 2014 Elsevier Ltd. All rights reserved.
cited By (since 1996)0
Keywords: Addition reactions; Antioxidant effect; Antioxidants; article; Ascorbic acid; carbon nuclear magnetic resonance; Chemical compounds; Competitive reactions; controlled study; electrophilicity; electrospray mass spectrometry; food preservative; glutathione; Glutathiones; heteronuclear multiple bond correlation; limit of quantitation; Nuclear magnetic resonance spectroscopy; Nucleophiles; Nucleophilic additions; nucleophilicity; oxidation; oxidation reduction reaction; Peptides; phloroglucinol; Protective action; proton nuclear magnetic resonance; quinone derivative; Quinones; Reaction intermediates; Reactivity (nuclear); Redox reactions; reversed phase liquid chromatography; Secondary product; Sulfur determination; Sulfur dioxide; synthesis; tannin; thiol derivative; Two-electron reduction; Wine